Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00253-015-6586-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic investigation of nutrient consumption and injection strategy in microbial enhanced oil recovery (MEOR) by means of large-scale experiments

Abstract: Microbial enhanced oil recovery (MEOR) depends on the in situ microbial activity to release trapped oil in reservoirs. In practice, undesired consumption is a universal phenomenon but cannot be observed effectively in small-scale physical simulations due to the scale effect. The present paper investigates the dynamics of oil recovery, biomass and nutrient consumption in a series of flooding experiments in a dedicated large-scale sand-pack column. First, control experiments of nutrient transportation with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
1
33
1
Order By: Relevance
“…Major SRB, such as Desulfobulbus and Desulfovirga , could reduce sulfate to ferrous sulfide, which acts as the cathode reacting with the metal to form an electrochemical cell resulting in the increase of corrosion rate . Regarding the EOR, a previous study found that the injected agents would be quickly degraded by microorganisms within a short distance before reaching oil-rich regions, which will reduce the efficiency of oil recovery . Therefore, researchers have attempted to achieve disinfection by adding microbiocides, but the disinfection efficiency has not been as good as expected. , An inadequate understanding of wellbore biofilms might be the major reason for this shortfall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major SRB, such as Desulfobulbus and Desulfovirga , could reduce sulfate to ferrous sulfide, which acts as the cathode reacting with the metal to form an electrochemical cell resulting in the increase of corrosion rate . Regarding the EOR, a previous study found that the injected agents would be quickly degraded by microorganisms within a short distance before reaching oil-rich regions, which will reduce the efficiency of oil recovery . Therefore, researchers have attempted to achieve disinfection by adding microbiocides, but the disinfection efficiency has not been as good as expected. , An inadequate understanding of wellbore biofilms might be the major reason for this shortfall.…”
Section: Discussionmentioning
confidence: 99%
“…29 Regarding the EOR, a previous study found that the injected agents would be quickly degraded by microorganisms within a short distance before reaching oilrich regions, which will reduce the efficiency of oil recovery. 52 Therefore, researchers have attempted to achieve disinfection by adding microbiocides, but the disinfection efficiency has not been as good as expected. 53,54 An inadequate understanding of wellbore biofilms might be the major reason for this shortfall.…”
Section: Discussionmentioning
confidence: 99%
“…It was used to evaluate the application potential of the exogenous surfactant-producing B. subtilis in facilitating the IMEOR process. Previous investigations have shown that the stimulation of indigenous microorganisms enhances oil recovery by 3.7–9.14 % ( Bao et al, 2009 ; Dong et al, 2015 ), and by 4.89–24 % in core-flooding tests with surfactant-producing bacteria and their metabolites ( She et al, 2011 ; Castorena-Cortes et al, 2012 ; Xia et al, 2012 ; Gudina et al, 2013 ; Al-Wahaibi et al, 2014 ; Arora et al, 2014 ; Song et al, 2015 ). In this study, the brines with nutrients and fermentation broth of B. subtilis M15-10-1 increased the oil displacement efficiency by 16.71%, which is higher than the 7.59% with nutrient injection only.…”
Section: Discussionmentioning
confidence: 99%
“…A major portion of these in vitro DNA molecules could be adsorbed by the porous reservoir with its enormous volume and specific surface area. Although some DNA molecules could avoid being adsorbed during the flow through the reservoir, they could be hydrodynamically sheared into short fragments (shorter than 1 kbp), especially with the long distance (260–300 m, several months of retention time for water and much more for macromolecules to flow through), narrow pore throats (mostly 1.4–3.5 μm, measured by mercury intrusion porosimetry) and high temperature (≥120 °C, considerably higher than DNA denaturing temperature). , Thus, during the cell extraction step the microfiltration membrane should not be able to collect soluble and reservoir-sheared DNA fragments, which therefore would not deviate the community detection of the wellhead samples.…”
Section: Methodsmentioning
confidence: 99%